2022
DOI: 10.2196/30512
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Records With Tablets at the Point of Care in an Internal Medicine Unit: Before-After Time Motion Study

Abstract: Background There are many benefits of nursing professionals being able to consult electronic health records (EHRs) at the point of care. It promotes quality and patient security, communication, continuity of care, and time dedicated to records. Objective The aim of this study was to evaluate whether making EHRs available at the point of care with tablets reduces nurses’ time spent on records compared with the current system. The analysis included sociod… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 35 publications
(80 reference statements)
1
4
0
Order By: Relevance
“…In this study, we found that two-thirds of the practical nurses who worked in home care or service housing perceived work time savings when they were using EHR/CIS on a mobile device. Similar work time savings have been reported in previous studies of healthcare professionals [14,20,21]. This study showed that documenting client data in a public area, for example in a corridor of a housing service, made work time savings over two times more likely than documenting at the (nurses') office, where computers are typically available.…”
Section: Comparison With Prior Worksupporting
confidence: 85%
See 3 more Smart Citations
“…In this study, we found that two-thirds of the practical nurses who worked in home care or service housing perceived work time savings when they were using EHR/CIS on a mobile device. Similar work time savings have been reported in previous studies of healthcare professionals [14,20,21]. This study showed that documenting client data in a public area, for example in a corridor of a housing service, made work time savings over two times more likely than documenting at the (nurses') office, where computers are typically available.…”
Section: Comparison With Prior Worksupporting
confidence: 85%
“…In the health care sector, saving work time is crucial because nursing professionals are tasked with a multitude of responsibilities in their daily practice. It is essential for them to have more time available for direct patient care and to minimize the time spent on indirect patient care activities, such as documentation [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, time-related data items can be used to measure how close to the event the data describes was the information recorded. Factors affecting timely capture of EHR-data include workflow inefficiencies, documentation burden, limited access to hardware, and interruptions [43][44][45][46][47][48]. Batch processing of data long after the event may indicate a lack of timeliness and affects other DQ dimensions such as completeness, accuracy, and validity [28,44,46,48,49].…”
Section: Data Quality Theorymentioning
confidence: 99%